The fate of ten - Lore, Pittacus (Penguin Books, 2016)
For years the Garde have fought the Mogadorians in secret. Now all of that has changed. The invasion has begun. If the Garde can't find a way to stop the Mogs, humanity will suffer the same fate as the Lorien: annihilation. There is still hope. When the Elders sent the Garde to Earth, they had a plan--one which the Garde are finally starting to understand. In the climax of The Revenge of Seven, a group of the Garde traveled to an ancient pyramid in Mexico known to their people as the Sanctuary. There they awoke a power that had been hidden within our planet for generations. Now this power can save the world ... or destroy it. It will all depend on who wields it.